(untitled) (Physical Education, Health and Social Sciences, 2025)
Healthcare-associated infections (HAIs) are a significant concern, particularly in high-risk settings like Pakistan. The choice of anesthetic agent for laryngeal mask airway (LMA) insertion can influence patient outcomes, including hemodynamic stability, risk of infection, and procedural efficiency. This study compares sevoflurane and propofol in terms of effectiveness, safety, and infection risk during LMA insertion. Objective of this study to evaluate and contrast the effects of sevoflurane and propofol on: Insertion time, Hemodynamic stability, Incidence of apnea, Potential immunomodulatory benefits (particularly in reducing LMA-associated infections) Methodology of Comparative analysis of two anesthetic agents 60 patients (30 in each group sevoflurane vs. propofol). Standardized hemodynamic monitoring. Outcome evaluations (insertion time, respiratory complications, hemodynamic stability). Statistical Analysis: p-value significance (<0.01) for key outcomes. Propofol provides faster insertion (74 ± 29s) than sevoflurane (127 ± 35s, p < 0.01) but has a higher apnea risk (32% vs. 0%, p < 0.01) and less hemodynamic stability. Sevoflurane, while slower, offers better hemodynamic control and potential immunomodulatory benefits against infections. Propofol is preferable for rapid procedures but carries a higher risk of respiratory depression. Sevoflurane is more suitable for hemodynamically fragile patients due to better stability and possible infection-reducing effects. Anesthetic choice should be tailored to patient-specific factors and surgical requirements to optimize outcomes.